Length–weight and length‐length relationships of four endemic fish species caught from Payra River, Southern Bangladesh. (19th December 2017) - Nahar, A.; Hanif, M. A.; Siddik, M. A. B.; Chaklader, M. R.; Islam, M. A.
Summary: The present study estimated the length–weight relationship (LWR) and length‐length relationships (LLR) of four fish species, Ompok pabo (Hamilton, 1822), Acentrogobius cyanomos (Bleeker, 1849), Acentrogobius caninus (Valenciennes, 1837) and Gagata cenia (Hamilton, 1822) collected from the Payra river over a period of 1 year between July 2015–June 2016 using set bag nets and cast nets with a mesh size of 0.5 cm and <0.5 cm, respectively. Altogether 593 individuals of O. pabo (59), A. cyanomos (221), A. caninus (240) and G. cenia (73) were sampled and studied. LWRs of O. pabo, A. cyanomos, and A. caninus are presented for the first time in Fishbase.